A carne mais barata do mercado é a (jovem) negra: percursos de (necro)políticas no Brasil - Braga Netto, Tathina Lucio (2018)
This research deals with the event of the capture of black young‟s deaths in the brazilian scenario by the State power that inserts this population in the political agenda. From contributions of Foucault's archegenealogy, we study State and government, through the conceptions of biopower and biopolitics that led us to a posture of mistrust about the new state concern. These notes directed us to problematize, from the analysis of documents, the conditions of truth that built the black youth as the target of public policies. To carry out this study, we selected nine documents that emerged from our objectives, in which we searched the search engines for documents with the key words: public policies for black youth and Juventude Viva; but we also start from the knowledge / references that underpinned Juventude Viva Plan. To build our analyzes, we followed some guiding questions: what conditions of possibility have made violence against black youth a State problem? What tensions have made possible the preventive public policies for violence against these young people? How does the knowledge-power that captures the deaths of this youth as a state problem build? These questions led us to some considerations: the resistance of the black movement as a founding element for the referral to preventive public policies of violence for black youth; the statistical data as triggers of the discussion of young blacks‟ mortality, but also as producer of opacity of this population; international bodies as the main motivators for the construction of public policies in the country. We carry out our analyzes based on the conceptualizations of Bio / Tanato / Necropolítica, problematizing how in our country there is a policy not only to manage lives, but to make them die. Thus, the Juventude Viva public policy functions as an instrument of inclusion in the exclusion, due to its decontextualized formulation and deficit structure, functioning as a way of operating marginalized lives